Early markers of athrosclerotic cardiovascular diseases and osteoporotic fractures in a postmenopausal woman (сlinical case) - М. А. Kolchina; O. V. Kosmatova; V. E. Novikov; I. A. Skripnikova (Klinicist)
The aim to demonstrate that subclinical atherosclerosis and vascular rigidity in a postmenopausal patient without clinical sings of cardiovascular disease and osteoporosis are connected with a decreased bone mass.Materials and methods. Patient O., 64 years old, was examined at the National Medical Research Center for Preventive Medicine within the program “Comprehensive assessment of total risks and early preclinical markers of osteoporosis and atherosclerosis complications”. No complaints during the examination were revealed. Laboratory tests were performed to evaluate blood lipids level, calcium-phosphorus metabolism, determine marker of bone resorption – CTX (β-crosslaps), measure levels of vitamin D and parathyroid hormone. Instrumental examinations included dual-energy x-ray absorptiometry of the spine and femoral neck, carotid ultrasound, applanation tonometry, multispiral computed tomography of coronary arteries with calcium score determination.Results. During outpatient examination, densitometry revealed decreased bone mineral density in the lumbar spine and in the femoral neck, corresponding to osteoporosis, carotid ultrasound identified atherosclerotic plaques, multispiral computed tomography of coronary arteries – coronary calcification, applanation tonometry – increased aortic stiffness.Conclusion. The clinical case is an example of early-detected preclinical signs of atherosclerosis and osteoporosis, as well as an increased risk of cardiovascular complications. Due to the high frequency of subclinical atherosclerosis, vessel wall state should be examined in women at the beginning of postmenopause. Signs of vascular stiffness and subclinical atherosclerosis give occasion to assess risk of fractures using the FRAX ® calculator and, if necessary, to diagnose bone mass loss using X-ray densitometry. Proposed algorithm can contribute to the early detection of cardiovascular diseases and at the same time improve fracture risk assessment.